The Lender of Last Resort Function after the Global Financial Crisis - Dobler, Marc (IMF Working Papers; Working Paper ;, 2016)
The global financial crisis (GFC) has renewed interest in emergency liquidity support (sometimes referred to as 'Lender of Last Resort') provided by central banks to financial institutions and challenged the traditional way of conducting these operations. Despite a vast literature on the topic, central bank approaches and practices vary considerably. In this paper we focus on, for the most part, the provision of idiosyncratic support, approaching it from an operational perspective; highlighting different approaches adopted by central banks; and also identifying some of the issues that arose during the GFC.